Kajian Manajemen Jaminan Mutu Pendidikan Menurut Dr. Muhsin Al-Mahdi Sa'id - Fawwaz, Syafiyqun; Inayati, Mahfida; Rahmawati, Rahmawati (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2024)
Accreditation as an educational unit will encourage schools to prepare themselves, not only for self-evaluation for the good of the future, but also as a means of public accountability. Quality education is a process of establishing and fulfilling management standards consistently and continuously, so that both consumers, producers and other interested parties obtain satisfaction. The education quality assurance system in activities focuses on continuous quality improvement, by measuring and assessing the quality of the education system, the performance of educational institutions, and the quality of study programs. According to Dr. Muhsin al-mahdi sa'id accreditation is an activity to assess the feasibility of a program in an educational unit based on predetermined criteria. In the quality assurance process there are several statements that must be fulfilled, as well as in the accreditation itself, which includes procedures, assessments and components that must be fulfilled, so that later the quality assurance management of education in educational institutions will develop well and receive a positive response. positive from the environment around the educational institution